Analysis of Thermal Stresses Induced in Radiant Tubes for Heat Exchanger Applications Using Finite Element Method - Ali, M. A.; Abbas, N.; Abbas, A.; Zahra, N. (The Nucleus, 2018)
In this research, the thermal stresses in the radiant tubes were analyzed using finite element method successfully. Thermal stresses are critical factor influencing on the strength of heat exchanger tubes. Radiant tube of Steel Alloy, Super 22H was analyzed by using finite element analysis. It is investigated that thermal stresses in radiant tubes faces different temperature gradients in axial, circumferential and radial directions. There are no significant thermal stresses in axial direction when there is linear temperature gradient. In addition, it is observed that considerable thermal stresses are induced with nonlinear temperature gradient in axial direction. In order to calculate thermal stresses in circumferential direction, the temperature variations in angular position is also applied. Radial thermal stresses are calculated by applying specific temperature difference between inner and outer radii. Localized heating & hot spot in inner or outer radii and bend in tubes are also major causes of thermal stresses.